A history of money : from AD 800 - Chown, John F., 1929- (London [England] ; New York : Routledge, 1996)
This book presents a detailed and surprising history of money from Charlemagne's reform in approximately AD800 to the end of the Silver Wars in 1896.
pt. 1. Money as coin -- pt. 2. The development of credit and banking -- pt. 3. Inconvertible paper money.
Includes bibliographical references (pages 273-290) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Money -- History; Credit -- History; Crédit -- Histoire; BUSINESS & ECONOMICS -- Money & Monetary Policy; Credit; Money; Samfundsvidenskab -- Økonomi; Electronic books; History